Proceso sancionatorio por contravención aduanera para mercancías sobrantes en importaciones a consumo de telas - Cárdenas Larrosa, Diana Elizabeth (2021)
The textile sector is one of the most dynamic in Ecuadorian imports, so the legal aspects involved in this process is one of the most important issues for all operators involved in this activity. Customs offenses, administrative contraventions, regulatory offenses, and consequent payment of fines and penalties are not a foreign issue to the clearance of import goods, but rather, fabrics, due to their packaging nature, are one of the items with the highest incidence of cases. Based on a study of the current customs regulations with a focus on the sanctioning processes in which textile importers frequently incur, it is determined that the way in which the bases should be structured to apply the respective fine of values to be charged for customs contraventions, literal n) of COPCI Art 190, reveals certain discrepancies in the texts that refer to this particular case...........